The Effect of Mind Mapping on Students’ Outcomes in Writing Observation Texts in Indonesian Language Learning - T. Mirza Elhyati Putri; Saprida; Basyarul Ulya (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the effect of the Mind Mapping learning model on students’ learning outcomes in writing observation texts in the Indonesian language subject. The research employed a quantitative experimental design, involving two class X groups from a senior high school. The experimental group was taught using the Mind Mapping model, while the control group received instruction through conventional learning methods. Data were collected through pre-tests and post-tests, and analyzed using statistical techniques to assess the impact of the intervention. The results showed that the average post-test score of the experimental group was significantly higher than that of the control group. Specifically, the t-test analysis yielded a p-value of 0.02 (p < 0.05), indicating a statistically significant difference between the two groups. This suggests that the Mind Mapping learning model positively influences students’ ability to understand and compose observation texts. The use of visual tools in the Mind Mapping strategy helps students organize ideas more effectively, enhancing their comprehension and creativity during the writing process. These findings align with previous research highlighting the effectiveness of Mind Mapping in improving student engagement and academic performance in language learning contexts. This study contributes to the growing body of evidence supporting the integration of creative and structured learning models like Mind Mapping into language instruction. However, the research was limited to a single school and a specific topic, suggesting that future studies should explore broader contexts and larger populations to validate and expand upon these findings.